Analysis Morphological Characters of Chalcorana chalconota (Schelgel, 1837) at Soraya and Ketambe Research Stations, Aceh - Fanny Lestari; Essy Harnelly; Djong Hon Tjong (Jurnal Penelitian Pendidikan IPA, 2026)
Chalcorana is a genus of amphibians that consists of species complexes which are difficult to distinguish morphologically. The difficulty in identifying species within this genus has prompted taxonomic research to utilize a more in-depth morphological approach in order to determine a more accurate taxonomic status and to examine the grouping of the Chalcorana genus originating from two different locations. This study used a principal component analysis (PCA) approach by measuring morphological characters. Based on the results of this study, it was found that different locations did not affect the variation in morphological characters, and therefore, no grouping was formed based on locality